PREDICTION OF COMBINING ABILITY AND HETEROSIS IN THE SELECTED PARENTS AND HYBRIDS IN RICE (Oryza Sativa.L) - Widyastuti, Yuni; Kartina, Nita; Rumanti, Indrastuti A.; Satoto, nFN (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2017)
Selection of parents based on their combining ability is an effective approach in hybrid breeding. Four CMS and four restorer lines were crossed in line x tester mating design to obtain 16 F1 hybrids rice. The 8 parental lines and 16 hybrids rice were planted in randomized complete block design with three replications at Kuningan and Muara field station of ICRR during 2012-2013. The results revealed that mean squares for GCA were significant for number of fertile spikelet per panicle, a thousand-grains weight, and 50% days of flowering. Mean squares for SCA were significant for plant height and grain yield. Parental lines exhibited the highest GCA effects for GMJ12A (line) and CRS703 (tester) for grain yield trait and revealed good potential to be used as parents for hybrid rice. Among all the crosses, GMJ6A/CRS707 and GMJ12A/CRS707 showed the greatest positive SCA effects for grain yield and had heterosis over better parent and midparent.